2005
DOI: 10.1177/0363546504271975
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Failure of Thermal Shrinkage for Laxity of the Anterior Cruciate Ligament

Abstract: Thermal shrinkage provides short-term benefit in the treatment of anterior cruciate ligament laxity but leads to catastrophic failure in the majority of patients at long-term follow-up. We can no longer recommend this procedure for the treatment of anterior cruciate ligament laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…Subsequent literature has found that the complications of electrothermal shrinkage exceeded its value, and consequently, thermal shrinkage is now rarely used. 17,46 In spite of the apparent clinical success, the patient was considered a failure for the purposes of this study. Given the subsequent literature, this treatment is not advocated, and this was our only experience with using it in such a setting.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent literature has found that the complications of electrothermal shrinkage exceeded its value, and consequently, thermal shrinkage is now rarely used. 17,46 In spite of the apparent clinical success, the patient was considered a failure for the purposes of this study. Given the subsequent literature, this treatment is not advocated, and this was our only experience with using it in such a setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although thermal shrinkage of a lax ACL is effective in shortening the ligament in the short term, longer term follow-up suggests an extremely high failure rate [16,33,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…L'alternative à une ligamentoplastie itérative est la remise en tension du ligament croisé. Dans ce but, Carter et al [15], Spahn et Schindler [16] et Halbrecht [17] ont eu recours au shrinkage. Cette technique consiste à appliquer une sonde thermique sur le ligament afin d'obtenir, par brûlure, une rétraction cicatricielle.…”
Section: Discussionunclassified
“…Cette technique consiste à appliquer une sonde thermique sur le ligament afin d'obtenir, par brûlure, une rétraction cicatricielle. À court terme, les résultats sont spectaculaires mais la fréquente récidive de la laxité et des cas de rupture ligamentaire [18,19] ont amené certains [17] à abandonner cette technique. D'autres [20] ont proposé d'ajuster les indications de cette technique aux tendons les mieux vascularisés, d'adopter un protocole de rééducation très prudent et se sont interrogés sur les paramètres physiques optimum de la sonde thermique employée.…”
Section: Discussionunclassified